Illness in breastfeeding infants relates to concentration of lactoferrin and secretory Immunoglobulin A in mother's milk. Issue 1 (20th January 2015) - Breakey, Alicia A.; Hinde, Katie; Valeggia, Claudia R.; Sinofsky, Allison; Ellison, Peter T.
Abstract : Background and objectives: This study aims to better understand the relationship between immune compounds in human milk and infant health. We hypothesized that the concentration of immune compounds in milk would relate to infant illness symptoms according to two possible theoretical paradigms. In the 'protective' paradigm, high concentrations of immune compounds prevent infant illness. The converse, the 'responsive' framework, posits that concentrations of immune compounds are elevated in response to infection. Methodology: Milk samples ( n = 110) and illness data were collected among the Toba of Argentina from 30 mother–infant dyads. Samples were assayed for two immune proteins, lactoferrin and secretory immunoglobulin A (sIgA). Generalized estimating equations were used to assess the relationship between immune composition of milk and symptoms of illness in infants. Results: Lactoferrin was positively associated with symptoms of illness in infants (odds ratios >1), both in the month preceding the sample collection and the subsequent month. sIgA was negatively associated with symptoms (odds ratios <1) in the preceding and subsequent months, an association which was particularly strong for gastrointestinal symptoms. Conclusions and implications: The two compounds investigated in our study had opposite relationships with symptoms of illness; the positive relationship between lactoferrin and illness lends support to our 'responsive' paradigm, and the negative relationship between sIgA and symptoms of illness was consistent with our 'protective' framework. That elevated lactoferrin is restricted to periods of illness suggests that there may be a cost to mother or infant associated with persistently elevated lactoferrin that is not incurred with elevated sIgA.